INVESTIGATIONS ON THE PHYSICAL MODEL OF THE PECULIARITIES OF THE INFLUENCE OF DUST ON THE QUALITY INDICATORS OF A GAS BURNING TORCH (Modern Problems of Metallurgy, 2021)
The oxygen converter process is accompanied by the release of a significant amount of gases, containing mainly the products of carbon oxidation reactions, which form a burning torch over the neck of the converter. A significant amount of dust of different composition and fraction is also released from the converter depending on the technological features of the blowing, the study and accounting of the impact of which is necessary to understand the qualitative characteristics of the torch and the converter process in general. The paper presents the results of a study on a physical model simulating a burning torch in a dusty environment, by introducing solid powders of various substances, on the qualitative indicators of torch combustion: visual and heat transfer. The supply of powders of sodium chloride, oxides of iron, silicon and aluminum, pure powders of iron, silicon and aluminum, carbon black and graphite to the burning torch was investigated. It was established that the introduction of various components into the torch with a temperature lower than the temperature of the torch, even with a possible visual increase in brightness characteristics, in particular when introducing sodium chloride or iron powder, reduce heat transfer from the torch due to the heat absorption for heating and combustion of introduced particles.
Keywords: physical modeling of postcombustion converter gas torch; powder materials; visual characteristics of torch; heat transfer